Inflexibility in Income Shifting: Implications, Detection and Remedies - Arnt Ove Hopland; Petro Lisowsky; Mohammed Mardan; Dirk Schindler (Center for Economic Studies and ifo Institute (CESifo), 2021)
This study develops theory and discusses implications of inflexibility in tax-motivated income shifting. We show that inflexibility to adjust income-shifting strategies within a tax year in response to losses implies that income-shifting incentives are based on the expected rather than the statutory tax rate differential. This has important implications for empirical research as our finding suggests that using the statutory tax rate differential risks underestimating the tax sensitivity of income shifting. We propose several empirical remedies to mitigate the estimation bias stemming from inflexibility, whenever a direct test is not feasible. The remedies vary in their data requirements, which allows future work on tax sensitivities of income to take into account inflexibility.
Keywords: F23; H25; H87; 330; income shifting; losses; debt shifting; transfer prices